Analisis Tayangan Sinetron Ikatan Cinta Terhadap Perilaku Sosial Masyarakat Palembang - Maya Afriani; Suryati Suryati; Lena Marianti (Social Science and Contemporary Issues Journal, 2023)
Soap operas are defined as dramas in a series of episodes that present stories from various characters simultaneously. The research is entitled Analysis of sinetron shows ikatan cinta in RCTI on the social behavior of the community palembang. Ikatan Cinta, an Indonesian soap opera created by MNC Pictures, had its television debut on RCTI on October 19, 2020 at 19.30 WIB. It's a soap opera directed by Doddy Djanas, has the genres of drama, romance, family and comedy. The screenwriters are Theresia Fransisca and Donna Rosamayna. The bond of love tells the story of two siblings, without them realizing it, they love the same man and in the end it causes family conflict. This study aims to determine the interest in watching soap operas Bonds of Love on RCTI and to find out how soap operas affect the social behavior of the people in  Palembang. The research used in this study began with data collection, recording, interpretation, application of the properties and objects studied included in a descriptive qualitative approach using the uses and gratifications theory. The subjects in this study were the people Palembang. This method forms data in the form of text or speech from each person's behavior that is seen. After analyzing the data, it was proven that the public was interested in watching soap operas that had an interesting storyline and visualization of the cast, and it was also proven that the soap opera Ikatan Cinta did not change behavior, but some followed the fashion style and the names of the characters from the soap opera Ikatan Cinta